Penerapan Strategi Pemasaran Digital Untuk Meningkatkan Penjualan Produk Umkm Pada Kelurahan Blitar - Nuruddin Islam, Muchammad; Indarto, Glenn Anggoro Pranana; Rohani, Choirina Kamilia; Arifin, Nanda Nur Humairoh; Sahdan, Muhammad Arlyen; Witjaksono, Gideon Setyo Budi (Universitas Gajah Putih, Indonesia, 2023)
Marketing strategy is a form of a company's plan in the marketing field to obtain optimal results. Information technology is becoming an integral part of all fields, profit or non-profit. Education, banking, government, art, telecommunications, law, and tourism all use information technology in some capacity. MSMEs in Blitar Village have problems in the application of digital marketing so that there needs to be a solution to these problems. The methods used are observation, interviews, focus group discussions, and demonstrations. The result of this activity is the delivery of material on the application of digital marketing such as the definition of digital marketing, examples of digital marketing, the impact of digital marketing, and a tutorial session on the use of e-commerce. The response from the Blitar Village MSME players who were also the audience was very positive and they intended to learn to apply digital marketing as soon as possible.